Compliance of private pharmacies in Uganda with controlled prescription drugs regulations: a mixed-methods study - Kamba, Pakoyo Fadhiru; Mulangwa, John; Kaggwa, Bruhan; Kitutu, Freddy Eric; Kaulukusi Sewankambo, Nelson; Tebasoboke Katabira, Elly; Byakika-Kibwika, Pauline; Odoi Adome, Richard; Bollinger, Robert Cyril (Substance abuse treatment, prevention, and policy, 2020)
Controlled prescription drug use disorders are a growing global health challenge in Sub-Saharan Africa. Effective supply chain regulations on dispensing and stock control are important for controlling this epidemic. Since compliance with these regulations in resource-limited countries is poor, there is need to understand its predictors in order to reduce the risk of prescription drug use disorders. Methods: A mixed-methods study utilizing a structured questionnaire and a simulated client guide was undertaken in Kampala and Mbale towns in Uganda. The questionnaire recorded self-reported dispensing and verified stock control practices and their covariates from 101 private pharmacies. The guide recorded actual dispensing practices from 27 pharmacies. Snowball sampling was done to enrich the sample with pharmacies that stock opioids. The mean compliance with good dispensing and stock control practices was calculated. Multivariate logistic regression analyses were applied to identify predictors of compliance.
Keywords: Controlled prescription drugs; Compliance predictors; Dispensing practices; Stock control practices; Opioids; Controlled drug regulations